New and interesting findings of the Lepidoptera from Astrakhan and Volgograd Territories (Southern Russia) - Sergei A. Rybalkin; Roman V. Yakovlev; Balázs Benedek (Zenodo, 2023)
Two species of moths, Drasteria christophi (Alphéraky, 1895) (Erebidae) and Protarchanara abrupta Eversmann, 1854 (Noctuidae), are reported from Russia for the first time; seventeen species of Notodontidae and Noctuidae are found as new for the fauna of Astrakhan and Volgograd Territories (Southern Russia). The first author thanks the director of the Kedr Hotel Vladimir V. Zhuravlev (Akhtubinsk), Sergey N. Yakovlev, and Dmitry I. Ponomar (Snezhinsk) for their help in organizing the field study.